If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 + 2x + -1 = 11 Reorder the terms: 7 + -1 + 3x + 2x = 11 Combine like terms: 7 + -1 = 6 6 + 3x + 2x = 11 Combine like terms: 3x + 2x = 5x 6 + 5x = 11 Solving 6 + 5x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5x = 11 + -6 Combine like terms: 6 + -6 = 0 0 + 5x = 11 + -6 5x = 11 + -6 Combine like terms: 11 + -6 = 5 5x = 5 Divide each side by '5'. x = 1 Simplifying x = 1
| 7.8+6=23.16 | | 7.8+6=23.16 | | 126+22+4x=180 | | 6x-15=x+5(3+x) | | (x+3)(x+3)=8x | | 20-16y=-19-19y | | p+4b=120 | | 2x+x+(x+2)=30 | | -208=-21x+212 | | -11-22=33 | | 7(4x-5)-4(6x-5)=-91 | | -2j-20=8j | | 8z=122 | | 65+90+5x=180 | | -3-y-X=0 | | 2x-8=-8x-24 | | 2(4-9w)= | | 57+51+9x=180 | | 6(-2y-16)-2y=-12 | | 6p+b=144 | | -18s+10=-17s | | (X+18)=(x+10) | | 18x-12=17x-2 | | 0=-x+5y | | 3(2z)=-3 | | -690=10(-7x+22) | | 5x-9x+3=17 | | 8x-4(-3+2)=-12 | | 2m+6n-9(5m-4n)= | | (2x-8)(2x-8)=44 | | 12x+15y=90 | | 100-66=31y-35y |